Competitive Exclusion and Metabolic Dependency among Microorganisms Structure the Cellulose Economy of an Agricultural Soil - Roland C. Wilhelm (American Society for Microbiology, 2021)
Our study reveals the ecogenomic traits of microorganisms participating in the cellulose economy of soil. We identified three major categories of participants in this economy: (i) independent primary degraders, (ii) interdependent primary degraders, and (iii) secondary consumers (mutualists, opportunists, and parasites).